Peningkatan Keterampilan Bermain Drama Dengan Menggunakan Teknik Oscar Brocket Pada Siswa Kelas XI-5 SMA Negeri 6 Palembang - Rawanti, Krisna; Lestari, Hikmah (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to enhance the drama playing skills of the 11th-grade students in SMA Negeri 6 Palembang using Oscar Brocket's techniques. It also seeks to integrate Oscar Brocket's techniques into their curriculum, expanding their repertoire of approaches. The method employed in this research is qualitative descriptive analysis supported by quantitative data to depict the drama playing abilities before and after the intervention. Qualitative analysis is utilized to record field observations and interview results, while quantitative data is obtained from drama playing evaluations before and after the intervention. Primary and secondary data sources are utilized in this research. Data collection techniques include observation, interviews with informants, recordings, and documentation. The data analysis is descriptive and qualitative. Drama learning necessitates a technique to enhance the learning process. Researchers and Indonesian language and literature teachers discussed techniques to enhance drama playing skills, with Oscar Brocket's technique being chosen. Oscar Brocket's technique facilitates students' understanding in drama playing by engaging them in various stages such as body exercises, voice exercises, imagination, concentration exercises, technique exercises, acting exercises, and skill-flexibility exercises. These techniques are applied progressively to prevent students from getting bored during drama learning. Students are trained to concentrate but in an enjoyable manner, encouraging them to imagine everything they can think of. They are also trained to act according to the characters in the scripts provided.